PENERAPAN E-COMMERCE PADA CV SUMBER SAHABAT - Antonius Antonius; Kartono Kartono; Erryanto Erryanto (INTEKSIS, 2023)
In a running system, CV Sumber Sahabat have computerization system that limited to purchase and sales which a simple report. CV Sumbe Sahabat still does not have web-base or e-commerce sales, where sales can only be done directly and through by sales. So that the author designed a web-base sales information system with the aim of helping CV Sumber Sahabat in wide scope of selling. The author uses descriptive research design as a research design, While the data collection method used is the method of interview, observation, and literature study. The author uses the Unified Modeling Language (UML) as a system analysis technique in sales information systems. The system design information technique used is the PHP Programming Language, DreamWeaver CS6 V 12.0 Editor and MySQL database design. The results of the research carried out in the form of a web-based sales information system at CV Sumber Sahabat which can be used to assist in selling goods in a wider scope. The page consists of inventory and sales transactions, inventory reports, daily sales reports and monthly sales reports on CV Sumber Sahabat in order to help employees obtain information and process better and quality data. Key Word: Designings Information Systems, Sales, Toy